The Silent Strain: Grip Strength, and Wrist/Hand Musculoskeletal Disorders among Meat Cutters - Jahangiri, Hamid; Ghasemi, Fatemeh; Zoaktafi, Mojgan; Salmani Nodooshan, Hamid; Vali, Mohebat; Daneshmandi, Hadi (La Medicina del Lavoro, 2026)
Background: Meat cutters are a working group engaged in awkward posture, repetitive motion, and forceful exertion in wrists/hands. This study was conducted a) to examine the prevalence of musculoskeletal symptoms among Iranian meat cutters, b) to assess the wrist musculoskeletal disorders risk assessment and hand grip strength. Methods: Ninety-five male meat cutters in Iran (≥ 1 year tenure) completed a demographic/occupational questionnaire, the Nordic Musculoskeletal Questionnaire (NMQ), and the Boston Carpal Tunnel Syndrome Questionnaire (BCTQ). Ergonomic risk was assessed via the ACGIH-TLV hand activity method, and maximum hand-grip force was measured. Results: With 69.5% reporting point prevalence and 70.5% reporting period prevalence of wrist/hand musculoskeletal symptoms, the study indicated that meat cutters had a significant prevalence of these symptoms. Most participants demonstrated mild to moderate severity in self-reported wrist symptoms while retaining asymptomatic functional status. The ACGIH-HAL assessment indicated most participants operated at or above the action level (AL), suggesting potential ergonomic risks. Moreover, The ACGIH-HAL ratio had a weak negative association with hand grip strength (β = − 0.0071, p = 0.12). Conclusions: These findings highlight the ergonomic challenges associated with meat-cutting tasks.